AB1070 Variations in the length of musculoskeletal temporary work disabilities in patients included in an early intervention program. (12th June 2018) - Lois Iglesias, A.; Bejerano, C.; de Toro Santos, F.J.
Abstract : Background: Musculoskeletal disorders cause in Spain 23% of temporary work disability (TD) and they are the first cause of permanent work disability (PD). A study of early intervention (early assessment and immediate treatment by a rheumatologist) reduced TD days (39%) and evolution to PD (50%) 1 . Using the "Fit for Work" European coalition led by AbbVie, the program is implemented nationwide. Objectives: The aim of this study is to analyse the variation in the number of days of sick leave in the patients included in an early intervention program comparing to usual average. Methods: Observational cross-sectional study of a hospital cohort of outpatients referred during 18 consecutive months. The patients were referred for the first time to the Rheumatology Early Intervention consultation program because of temporary work disabilities due to musculoskeletal disorders. All of them received medical treatment; and underwent joints ultrasound, joint injections and learned exercises when needed. Patients whose disabilities were due to trauma or surgery were not included in the study. Results: We evaluated 270 patients with a mean age of 48.9 years. 64% were women. The most frequently reported diseases were lumbar/sciatic pain (28.5%), shoulder pain (20%), neck pain (8%), knee pain (5.6%) and other arthralgias and tendinopathies (20%). All patients received medical treatment, 38.5% underwent ultrasound examination and 19, 2% received joint injections. The pathologies with longest lengths of TD after the first visit to the rheumatologist were lumbar/sciatic pain (mean 40.6 days), neck pain (mean 33 days) and shoulder pain (mean 23.8 days). If we compare this data with the existent control group from San Carlos Hospital (Madrid), we can see a decrease of the days in sick leave of 29, 5% in lumbar/sciatic pain (from 57.6 to 40.6 days), 11, 7% in neck pain (from 37.4 to 33 days) and 36, 3% in shoulder pain (from 37.4 to 23.8 days). Conclusions: Early intervention by rheumatologists in patients with temporary work disability due to musculoskeletal disorders reduces the length of sick leaves. A quick diagnosis and assessment by specialists can improve the patient outcomes saving costs to health system. Reference: [1] : Abasolo L, et al. A health system program to reduce work disability related to musculoskeletal disorders. Ann intern Med. 2005Sep 20; 143 (6):404–14. Disclosure of Interest: None declared